Analysis of Operational Risk Management Based on the Waqf Core Principles Approach: A Case Study of Quran Waqf Board Solo - Fitri Lestari, Arum; Satar, Muhammad; Eliya Rokhmah, Betty (Program Studi Manajemen Zakat dan Wakaf, 2025)
Qur'anic waqf, as a form of social and spiritual philanthropy, plays a vital role in supporting religious literacy and social welfare. However, its operational management faces significant challenges, including distribution errors, lack of transparency, and maintaining public trust, which can hinder its effectiveness in serving beneficiaries. This study examines the application of the Waqf Core Principles (WCP) framework in managing operational risks at the Solo Qur'anic Waqf Board (BWA). Employing a descriptive qualitative approach, this research collects data through direct observations and in-depth interviews with the branch manager of BWA Solo. The findings indicate that BWA Solo has successfully implemented key WCP principles, particularly in ensuring financial transparency, accountability, and equitable waqf distribution. Nevertheless, challenges persist, including inconsistencies in risk management and potential mismanagement. Moreover, the increasing complexity of waqf operations, driven by digitalization, necessitates continuous improvements in governance and security measures. This study highlights the crucial role of WCP in strengthening the operational efficiency and credibility of waqf institutions. The research also suggests enhancing risk mitigation strategies by leveraging technology, such as Artificial Intelligence (AI), to improve monitoring and reporting mechanisms. By addressing these challenges, waqf institutions can enhance their sustainability and societal impact, fostering greater trust and participation in waqf-based initiatives.